Thanks for that elegant defense - Mills, R; Mills, Rebecca May (2000)
﻿ The end of the seventeenth century and the beginning of the eighteenth saw many women writers from numerous social ranks, political affiliations and religious denominations reading, writing, circulating and publishing polemical prose and poetry in defence of their sex. During this surge of protofeminist activity, many of these women decried 'Customs Tyranny' by advocating a more egalitarian status for themselves, especially in regard to marriage, education and religion. This thesis, then, is a socio-historic study of the lives and writings of several polemical women writers, namely, Mary Astell (1666-1731), Mary, Lady Chudleigh (1656-1710) and Elizabeth Thomas (1675-1731). It also considers how and why protofeminism evolved in the late seventeenth century and reached a climax between 1694, when Astell published A Serious Proposal to the Ladies, and 1710, when Chudleigh published Essays upon Several Subjects. Until now, scholars of early women writers have labelled Astell the foremost English feminist of her day. Consequently, many of her contemporary protofeminist writers have been neglected. By contextualizing their lives and texts within the political and literary activity at the turn of the eighteenth century, this thesis ultimately argues that women polemicists, such as Chudleigh and Thomas, who followed Astell into print, were not merely echoes and disciples. Rather, they furthered the evolution and secularization of a genre that anticipates feminism proper, which began to develop in the late eighteenth and early nineteenth centuries. In order to uncover and rediscover the personal and professional details of these women's lives their class, education, friendships and patronage relationships this thesis relied heavily upon material evidence such as letters, parish records, legal records, prison records and wills. As a result, it combines feminist, materialist inclinations with traditional methodology, such as historical and archival research.